Impact of Rice Field Conversion Effectiveness on the Availability of Rice in Jakarta Province From 1981 to 2023 - Guruh Putra, Ibnu; Iqbal, Muhammad; Roi Bafih, Achmad; Rohma Wati, Dewi (Agricultural Science, 2024)
This study examines the impact of rice field conversion on the availability of rice in Jakarta Province from 1981 to 2023. Over this period, Jakarta experienced rapid urbanization, transforming agricultural land especially rice field area into urban infrastructure. The rice field area shrank from 7,720 hectares in 1981 to only 341 hectares in 2023, with rice production declining from 70,387 tons to 2,674 tons. Meanwhile, rice demand surged from 474 million kilograms in 1981 to 874 million kilograms in 2023 due to population growth. The study employs secondary data analysis, utilizing regression models to assess the influence of population density and productivity on rice field area. The results indicate that population density is the primary driver, with every unit increase leading to a loss of 104 hectares of rice field area. Conversely, productivity improvements had no significant impact on land size. The findings of current study highlight a growing dependency on external food sources, exposing Jakarta to food security risks. This research underscores the urgency of sustainable land management policies to balance urbanization and agricultural preservation. Recommendations include integrating land-use planning with food security strategies to ensure a stable and sufficient food supply for Jakarta's growing population.